Accelerated development of cerebral small vessel disease in young stroke patients. (20th September 2016) - Arntz, Renate M.; van den Broek, Steffen M.A.; van Uden, Inge W.M.; Ghafoorian, Mohsen; Platel, Bram; Rutten-Jacobs, Loes C.A.; Maaijwee, Noortje A.M.; Schaapsmeerders, Pauline; Schoonderwaldt, Hennie C.; van Dijk, Ewoud J.; de Leeuw, Frank-Erik
Abstract : Objective: To study the long-term prevalence of small vessel disease after young stroke and to compare this to healthy controls. Methods: This prospective cohort study comprises 337 patients with an ischemic stroke or TIA, aged 18–50 years, without a history of TIA or stroke. In addition, 90 age- and sex-matched controls were included. At follow-up, lacunes, microbleeds, and white matter hyperintensity (WMH) volume were assessed using MRI. To investigate the relation between risk factors and small vessel disease, logistic and linear regression were used. Results: After mean follow-up of 9.9 (SD 8.1) years, 337 patients were included (227 with an ischemic stroke and 110 with a TIA). Mean age of patients was 49.8 years (SD 10.3) and 45.4% were men; for controls, mean age was 49.4 years (SD 11.9) and 45.6% were men. Compared with controls, patients more often had at least 1 lacune (24.0% vs 4.5%, p < 0.0001). In addition, they had a higher WMH volume (median 1.5 mL [interquartile range (IQR) 0.5–3.7] vs 0.4 mL [IQR 0.0–1.0], p < 0.001). Compared with controls, patients had the same volume WMHs on average 10–20 years earlier. In the patient group, age at stroke (β = 0.03, 95% confidence interval [CI] 0.02–0.04) hypertension (β = 0.22, 95% CI 0.04–0.39), and smoking (β = 0.18, 95% CI 0.01–0.34) at baseline were associated with WMH volume. Conclusions: Patients with a young stroke have a higher burden of small vessel disease than controls adjusted for confounders. Cerebral aging seems accelerated by 10–20 years in these patients, which may suggest an increased vulnerability to vascular risk factors.